Ovarian preservation in children for adenexal pathology, current trends in laparoscopic management and our experience - Preet Agarwal; Prakash Agarwal; Rajkishore Bagdi; Subramaniam Balagopal; Madhu Ramasundaram; Balamourougane Paramaswamy (Wolters Kluwer Medknow Publications, 2014)
Aims: Primary cysts and tumors of the ovary alongwith torsion are often regarded as an indication for open oophorectomy because of the fear of leaving an ischemic organ inside and chances of recurrence. We wish to report our experience of both modalities of management where we initially removed adenexal torsion by either laparoscopic salpingo-oophorectomy or oophorectomy, but later followed a more conservative approach of adenexal lesion removal with ovarian preservation. Materials and Methods: Retrospective review of clinical records of patients with ovarian pathology who were managed laparoscopically. Results: 46 cases of pediatric ovarian pathology were managed between March 2006 and March 2013 in two centers by a team of surgeons. The age ranged from 1 days to 18 years (average 14.3 years) and the pathology varied from 30 cases of a simple ovarian cyst with torsion, 3 cases of ovarian torsion without any cyst, 7 cases of a dermoid cyst with torsion in all, 1 case of secreting ovarian tumor and 5 cases of a paraovarian cyst with torsion. All patients had a normal tumor marker except 1 girl with a functional ovarian tumor who had elevated LDH and estrogen levels alongwith suppressed LH and FSH. In the initial period of our study we did 1 salpingo-oophorectomy for a suspected complex lesion and two oophorectomies for torsion with a simple cyst. In the later part of our study we performed laparoscopic cystectomy and ovarian preservation in 40 cases, including 7 cases of dermoid, where we performed laparoscopic detorsion with dermoid cystectomy and ovarian preservation in the same sitting. In three cases of chronic torsion who presented to us late, we could not preserve the ovary and had to resort to salpingo-ophorectomy. Histology showed a simple corpus luteal and follicular ovarian cyst in 31 cases, a paraovarian cyst in 5 cases with mature teratoma in 7 cases. Twenty-five patients with ovarian preservation following detorsion were subjected to follow-up ultrasound, who were found to have normal shape, size and blood flow compared to the contra lateral side. Conclusion: We outline our experience from the management of 46 cases of various ovarian pathologies with and without ischemia and found that ovarian torsion with a benign pathology and ischemia is not a contraindication for ovarian preservation, as pointed out in the current literature.